G312(P) Dmd audit abstract for (p) presentation. (12th March 2018) - Sampath-Arutperumselvi, V; DeGoede, C
Abstract : Objective: Diagnosis and management of Duchenne muscular dystrophy: Use of published standards, to audit regional service. Background: In 2010 standards of care for diagnosis and management of Duchenne muscular dystrophy were published in Lancet Neurology. 1, 2 Our regional neuromuscular service was set up in 2013, largely supported and driven by these standards. We evaluated the service against these standards. Methodology: Retrospective audit looking at the management of 31 DMD patients. Data was collected by reviewing case notes over a period of 14 months. Results: All patients (n=31, 100%) had genetic testing to confirm the diagnosis and received chicken pox vaccination or had their immune status checked before starting steroids.24 patients (80%) had attended specialist clinic appointment every 6 months. North Star Ambulatory assessment recommended every 6 months was done in 3 patients (20%). Annual serum Vitamin D level was done in 17 patients (58%). Annual DEXA scan for patients on chronic glucocorticoid therapy was done in 4 patients (14%). Spinal X-ray for patients with back pain or Kypho-scoliosis was done in 77% of the patients (n=10). 30 patients (97%) received Vitamin D supplements and 28 patients (93%) had echocardiograms done as per recommendation. 71% of the ambulatory patients (n=10)received the recommended respiratory assessments but none of the non-ambulatory patients received all the recommended respiratory assessments. 75% of non-ambulatory patients with poor lung function (n=3) received the recommended awake end tidal CO2 level measured. Conclusions: Vital areas for improvement were identified and an action plan has been formulated. Main areas for improvement included availability of the neuromuscular physiotherapist to perform 6 monthly North Star ambulatory assessment and respiratory assessment, and improving access to DEXA scan. The latter involves training radiology staff to perform scans on children. The published standards have been very helpful in the development and subsequent evaluation of the regional muscle service. References: . Nushby, et al. Diagnosis and management of duchenne muscular dystrophy, part 1: Diagnosis, and pharmacological and psychological management. Lancet Neurology2010;9:77–93. . Bushby, et al. Diagnosis and management of duchenne muscular dystrophy, part 2: Implementation of multidisciplinary care. Lancet Neurology2010;9:177–189.